Narapidana Wanita dalam Penjara: Kajian Perilaku Sosial Narapidana Wanita - Meilya, Ika Rizqi; Hanafi, Syadeli; Siregar, Herlina; Fauzi, Ahmad (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
The purpose of this study is to explain how the life, types of crime and background of a woman committing a crime; public view; forms of discriminatory behavior in society; as well as the factors that influence the community's discriminatory behavior towards the status of female ex-prisoners. This study uses a qualitative approach and descriptive methods, the location of this research is in the class IIA penitentiary, Tangerang city. Data collection techniques using interviews, documentation and observation. The research subjects were prison heads and managers, assisted residents, and the community. The data collection technique is done by interview, observation, documentation. The results of this study are (1) activities of female prisoners in prison, including: religion, sports, life skills training, equality programs (packages A, B, C), and the arts; (2) the type of crime and the background of a woman committing a criminal act the highest cases are narcotics, secondly child protection, corruption, theft, murder, fraud, and other cases with a small percentage such as decency, persecution, forgery, kidnapping; (3) the public's view of the status of female ex-prisoners varies depending on the cases that ensnared them. (4) Forms of discrimination committed by the community against female ex-prisoners include: negative views, stigma in the form of stereotypes, and injustice. (5) the factors that cause discrimination by the community against female ex-prisoners are caused by: past historical background, socio-cultural and situational developments, personality factors in the frustration of certain people or social groups, and differences in beliefs.